Inactivation of a Mismatch-Repair System Diversifies Genotypic Landscape of Escherichia coli During Adaptive Laboratory Evolution - Kang, Minjeong; Kim, Kangsan; Choe, Donghui; Cho, Suhyung; Kim, Sun Chang; Palsson, Bernhard; Cho, Byung-Kwan (Frontiers in Microbiology, 2019)
Adaptive laboratory evolution (ALE) is used to find causal mutations that underlie improved strain performance under the applied selection pressure. ALE studies have revealed that mutator populations tend to outcompete their non-mutator counterparts following the evolutionary trajectory. Among them, mutS-inactivated mutator cells, characterized by a dysfunctional methyl-mismatch repair system, are frequently found in ALE experiments. Here, we examined mutS inactivation as an approach to facilitate ALE of Escherichia coli. The wild-type E. coli MG1655 and mutS knock-out derivative (ΔmutS) were evolved in parallel for 800 generations on lactate and glycerol minimal media in a serial-transfer experiment. Whole-genome re-sequencing of each lineage at 100-generation intervals revealed that 1) mutations emerge rapidly in the ΔmutS compared to in the wild-type strain; 2) mutations were more than four-fold higher in the ΔmutS strain at the end-point populations compared to the wild-type stain; and 3) a significant number of random mutations accumulated in the ΔmutS strains. We then measured fitness of the end-point populations on an array of non-adaptive carbon sources. Interestingly, collateral fitness increases on non-adaptive carbon sources were more pronounced in the ΔmutS strains than the parental strain. Fitness measurement of single mutants revealed that the collateral fitness increase seen in the mutator lineages can be attributed to a pool of random mutations. Together, this study demonstrates that short-term mutator ALE extensively expands possible genotype space, resulting in versatile bacteria with an elevated fitness levels across various carbon sources.